PELUANG DAN TANTANGAN DALAM PEMBANGUNANINDONES Permasalahan dan Upaya Mengatasinya - Azhar Kasim (Universitas Riau, 2008)
Indonesia is experiencing protracted and multi-dimensional predicaments, and ongoingvicious circles in almost all aspects of societal life. The dynamic of existing political, legal,economic and public administration systems are unable to overcome this problem. In order tobreak through these vicious circles innovative public policies as leverages are needed. In ademocratic system, processes of change are initiated by people at the bottom and go up throughthe political mechanism to the policy decision makers. In Indonesia, the democratic politicalprocess does not work effectively. In reality, the process of policy decision making is still dominatedby the ruling elite, therefore, public policy does not reflect the demand of the people butrather the interest of the elite. We need a strong and visionary national leadership for creating andimplementing the process of dynamic capability among the people as stakeholders. Dynamiccapability is the process of thinking ahead, thinking again and thinking across in order to initiatethe process of public policy transformation, especially in the field of a legal system, qualityeducation, and public administration which can facilitate the national development program.